Inhibitory effect of glyceollins on vasculogenesis through suppression of endothelial progenitor cell function. Issue 10 (19th June 2013) - Choi, Jin‐Hwa; Nguyen, Minh Phuong; Jung, Seok‐Yun; Kwon, Sang‐Mo; Jee, Jun‐Goo; Bae, Jong‐Sup; Lee, Sangkyu; Lee, Min Young; Lee, You‐Mie
<x xml:space="preserve">Abstract</x> Scope Endothelial progenitor cells (EPCs) are derived from hematopoietic stem cells, and have the ability to differentiate into mature endothelial cells and contribute to neovascularization. Glyceollins are a type of phytoalexin produced in soybeans under stress conditions. The aim of this study is to determine the effect of glyceollin treatment on EPCs during early tumor vasculogenesis. Methods and results We found that glyceollin treatment significantly decreased the number of EPC colony‐forming units in human cord blood‐derived AC133+ cells and mouse bone‐marrow‐derived c‐Kit+/Sca‐1+/Lin− cells. Glyceollin treatment diminished the number of lineage‐committed EPC cells in a dose‐dependent manner (1–20 μM). Glyceollin treatment inhibited EPC migration, tube formation and the mRNA expression of angiopoietin‐1 (Ang‐1), Tie‐2, stromal‐derived factor‐1 (SDF‐1), C‐X‐C‐chemokine receptor‐4 (CXCR4), and endothelial nitric oxide synthase (eNOS) in cultured EPCs. Glyceollin treatment suppressed activation of Akt, Erk, and eNOS induced by SDF‐1α or vascular endothelial growth factor (VEGF). Treatment with 10 mg/kg glyceollins significantly reduced the number of tumor‐induced circulating EPCs and the incorporation of EPCs into neovessels in bone marrow transplanted mice. Conclusion These results suggest that glyceollins inhibit the function of EPCs in tumor neovascularization. Glyceollins from soybean elicitation could be beneficial in prevention of cancer development via vasculogenesis.